2023
DOI: 10.1039/d3dt01451g
|View full text |Cite
|
Sign up to set email alerts
|

Catching up with tetrazines: coordination of Re(i) to 1,2,4-triazine facilitates an inverse electron demand Diels–Alder reaction with strained alkynes to a greater extent than in corresponding 1,2,4,5-tetrazines

Abstract: Inverse electron demand Diels Alder (IEDDA) reactions of 1,2,4-triazines are of interest to biorthogonal chemistry but suffer from slow kinetics. It is shown here that coordination of Re(I) to a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…26 Another approach is to decrease the electron density on the triazine core by the coordination of heavy metal ions to the triazine core. 27,28 Yet the reactivity of triazines in iEDDA reactions with strained alkynes and trans -alkenes is generally significantly lower than that of similar tetrazines. Thus, the search for an optimal diene system for bioorthogonal iEDDA reactions continues (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…26 Another approach is to decrease the electron density on the triazine core by the coordination of heavy metal ions to the triazine core. 27,28 Yet the reactivity of triazines in iEDDA reactions with strained alkynes and trans -alkenes is generally significantly lower than that of similar tetrazines. Thus, the search for an optimal diene system for bioorthogonal iEDDA reactions continues (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lo et al demonstrated this effect in tetrazine complexes, 4 while we describesimilar behaviour of Ir(III) complexes of 1,2,4triazines. 15,16 Importantly, both the tetrazine and the triazine systems also show luminogenic behaviour in reactions with BCN derivatives. 4,15 We report the synthesis and evaluation of novel iridium(III) complexes that can participate in IEDDA reaction.…”
Section: Introductionmentioning
confidence: 99%